Proposed Scheduling of Preventive Maintenance on Co₂ Welding Machines Based on Reliability Analysis and FMEA Methods at PT. Sub Automotive - Umar Dana, Rizko; Suhara, Ade; Roban, Roban; Sayuti, Muhamad (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2025)
As the industry increases its dependence on production machinery, machine maintenance is a vital aspect in ensuring the smooth operation of the company. PT. Sub Automotive, as a dump truck carousel manufacturer, faces the problem of high downtime in CO₂ welding machines caused by component damage. This research aims to design an appropriate preventive maintenance schedule to reduce the frequency of damage and increase machine availability. The methods used include Mean Time Between Failure (MTBF), Mean Time To Repair (MTTR), and Overall Availability (Ao) analysis, as well as the Failure Mode and Effect Analysis (FMEA) approach to identify critical components based on the Risk Priority Number (RPN) value. The results showed an average machine availability value of 97%, exceeding the global standard of 90%. The components with the highest RPN values, namely the Control PCB (180), Nozzle (168), and Contact Tip (126), were identified as the main contributors to downtime. Based on these results, preventive maintenance recommendations were prepared focused on these components to improve the overall reliability of the system